Pengembangan Media Evaluasi Pembelajaran Matematika Berbasis Aplikasi Quizizz dengan Soal PISA Konten Quantity - Kristanto, Bagas Prima; Yunianta, Tri Nova Hasti (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Jambi, 2021)
The development of learning evaluation media is important as an innovation for teachers in online learning during a pandemic. This study aims to develop a learning evaluation media based on the Quizizz application with valid and practical PISA math questions with quantity content so that it is feasible to use. The method used is research and development level 1 where this research will develop and validate the product without spreading the product. The method stages in research and development consist of determining potentials and problems, gathering information and studying literature, then designing the product finally validating the product. The product design stage produces a product that is then validated by the media and material by experts in their fields and practicality by mathematics teachers. The results of this study indicate that the learning evaluation media based on the Quizizz application with the PISA mathematics questions of the Quantity content can be said to be valid and practical so that they are feasible to use. The average percentage of the assessment shows that 90.6% of this media is valid and 91.3% practical, so this product is said to be suitable for use.